Index-based livestock insurance - Barrett, Christopher (Henry Stewart Talks, 2019)
This case study describes the development of index-based livestock insurance (IBLI) in northern Kenya and southern Ethiopia. This insurance is designed to counter drought shocks around the horn of Africa and has been markedly successful in mitigating drought-related humanitarian disasters in this region.